2022
DOI: 10.3390/molecules27144374
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Uses, Phytochemistry, Toxicology, and Pharmacological Properties of Euphorbia neriifolia Linn. against Infectious Diseases: A Comprehensive Review

Abstract: Medicinal plants have considerable potential as antimicrobial agents due to the presence of secondary metabolites. This comprehensive overview aims to summarize the classification, morphology, and ethnobotanical uses of Euphorbia neriifolia L. and its derived phytochemicals with the recent updates on the pharmacological properties against emerging infectious diseases, mainly focusing on bacterial, viral, fungal, and parasitic infections. The data were collected from electronic databases, including Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Several studies have demonstrated the antimicrobial and antimycobacterial activities, respectively, from E. neriifolia and Cissampelos mucronate containing simiarenol as one of the present compounds in their extracts. Also, one recent research has shown this plant's probable efficacy in treating a range of infectious diseases such as COVID-19, which might be related to this natural constituent but further investigations should be carried out to determine these claims and specifically relates them to simiarenol [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the antimicrobial and antimycobacterial activities, respectively, from E. neriifolia and Cissampelos mucronate containing simiarenol as one of the present compounds in their extracts. Also, one recent research has shown this plant's probable efficacy in treating a range of infectious diseases such as COVID-19, which might be related to this natural constituent but further investigations should be carried out to determine these claims and specifically relates them to simiarenol [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…According to a literature search, a total of twenty-two plants from around India were discovered to be effective against dengue fever. Further clinical trials are necessary to validate the safety, effectiveness, and method of action of additional plants that have been reported [ 46 , 47 ]. During the validation research, these plants may undergo testing either individually or in various combinations to gain a deeper understanding of their synergistic effects in terms of both efficacy and safety ( Table 2 ).…”
Section: Dengue-treating Plants From Folklore and Herbal Medicinementioning
confidence: 99%
“…Therefore, there is an urgent need to develop novel anticancer compounds with fewer side effects, as well as to combat multi-drug resistance [3]. Since the dawn of human civilization, plants have been used as remedies to treat various diseases [4]. In recent years, medicinal plants, with their bioactive compounds, have played a significant role in discovering and developing therapeutic agents [5][6][7].…”
Section: Introductionmentioning
confidence: 99%